Living with an adult who has diabetes: Qualitative insights from the second Diabetes Attitudes, Wishes and Needs (DAWN2) study. (June 2016) - Stuckey, Heather L.; Mullan-Jensen, Christine; Kalra, Sanjay; Reading, Jean; Wens, Johan; Vallis, Michael; Kokoszka, Andrzej; Malek, Rachid; Kovacs Burns, Katharina; Piana, Natalia; Skovlund, Søren E.; Peyrot, Mark
Highlights: DAWN2 captures the qualitative analysis of family member (FM) experiences with diabetes. FMs worry about daily struggles, such as hypoglycemia and employment instability. Diabetes negatively affects dynamics of family relationship, creating strain. FMs have some support resources, but would like more. The person with diabetes provided inspiration for FM to make positive life changes. Abstract: Aims: The second Diabetes Attitudes, Wishes and Needs (DAWN2) study identified the experiences of family members who support adults living with diabetes. Methods: Participants were 2057 adult family members living with the person with diabetes from 17 countries. Qualitative data were responses to open-ended survey questions about how living with a person with diabetes has impacted family members and the ways they choose to be involved in the diabetes care for the person with whom they live. Emergent coding with input from multinational collaborators identified thematic content about psychosocial aspects. Results: Family members wanted to do what was best for the person with diabetes and help in whatever way possible. Four themes branched from that principle: (1) family members worry about day-to-day struggles of the person with diabetes, such as hypoglycemia and employment stability; (2) diabetes negatively affects the person with diabetes–family member relationship, creating an emotional strain and shift in relationship; (3) family members have some support resources to deal with the burdens and lifestyle changes of diabetes, but would like more; and (4) the person with diabetes has provided inspiration to the family member, and helped the family member make positive life changes in eating healthier. Conclusions: These data provide insight into the ways that family members experience living with diabetes, including their challenges, motivations and intentions in supporting their person with diabetes. Family members speak eloquently and with emotion about their role in a family with diabetes.